2015
DOI: 10.7146/hjlcb.v27i54.22947
|View full text |Cite
|
Sign up to set email alerts
|

The Reconceptualization of Academic Discourse as a Professional Practice in the Digital Age: A Critical Genre Analysis of TED Talks

Abstract: This paper explores how academic discourse is reconceptualized as a professional practice via the web-mediated genre of TED talks (Technology, Entertainment and Design), popularizing speeches delivered by experts in fi elds that range from the 'hard' disciplines to the social sciences and the humanities. More precisely, this study compares two corpora of academic spoken discourse, i.e., a corpus of transcribed TED talks given by academics (TED_ac) and a corpus of university lecture transcripts (MICASE_lect) dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…The clue is to introduce your topic, explain why you care deeply about it and convince the audience that they should care too. Results of later studies (Caliendo, 2014;Scotto di Carlo, 2014;Compagnone, 2015) have corroborated these views. For example, a comparative study by Scotto di Carlo (2014) has shown how persuasive appeals through ethos, pathos and logos are remarkably different in a TED talk and a conference presentation dealing with the same topic and delivered by the same speaker.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The clue is to introduce your topic, explain why you care deeply about it and convince the audience that they should care too. Results of later studies (Caliendo, 2014;Scotto di Carlo, 2014;Compagnone, 2015) have corroborated these views. For example, a comparative study by Scotto di Carlo (2014) has shown how persuasive appeals through ethos, pathos and logos are remarkably different in a TED talk and a conference presentation dealing with the same topic and delivered by the same speaker.…”
Section: Introductionmentioning
confidence: 74%
“…Within research dissemination talks, TED talks have received increasing attention. Caliendo (2014) and Compagnone (2015) acknowledge their multimodal nature noting that this genre combines different semiotic modes (i.e. spoken, written, video and audio).…”
Section: Introductionmentioning
confidence: 99%
“…The impersonal authoritative references, together with the use of war metaphor, highlights political communicative purpose of TED talks (cf. Compagnone, 2015 ) and make them a less likely academic-style genre, where self-mention contributes to speakers’ construction of texts and acceptance of ideas.…”
Section: Discussionmentioning
confidence: 99%
“…It further states that the professional practice, interdiscursivity and multi-perspectives are the core of CGA, making its framework clearer and more easily applied. In recent years, CGA theory has attracted increasing attention in research on professional discourse, for example, business discourse (Lung, 2017; Yeung, 2013), institutional discourse (Fage-Butler, 2015; Levina and Orlikowski, 2009; Svenonius, 2013), social network discourse (Motta-Roth and Marcuzzo, 2010) and academic discourse (Compagnone, 2015), among others. With the contribution made by CGA research so far, this study tries to expand the application of CGA in the analysis of MD&A, an under-investigated discourse, in order to better understand its interdiscursivity, the nature and function of discursive practices of business professionals.…”
Section: Critical Genre Analysismentioning
confidence: 99%